BUSINESS AND MANAGEMENT TEACHERS' PERCEPTION OF THE INDEPENDENT LEARNING CURRICULUM AT STATE VOCATIONAL SCHOOL 1 SIGLI, PIDIE DISTRICT - Ayu Putri; Darmi Darmi; Maisura Maisura (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jabal Ghafur, 2026)
ABSTRACTThe study entitled